Profile of Side Effects of Chemotherapy in Non-Small Cell Lung Cancer Patients (NSCLC) Undergoing Chemotherapy at Dr. M. Djamil General Hospital, Padang, Indonesia - Isnaniyah Usman; Sabrina Ermayanti; Afriani Afriani (HM Publisher, 2022)
Background: Chemotherapy is one of the treatment options for lung cancer at any stage. Side effects due to chemotherapy are still a problem in the treatment of lung cancer patients. Chemotherapy drugs have different side effects according to their pharmacokinetics and pharmacodynamics. This study aimed to determine the side effects of both hematological and non-hematological chemotherapy in non-small cell lung cancer patients treated at the lung ward of Dr. M. Djamil General Hospital, Padang, Indonesia, from 2017 to 2019. Methods: This was a descriptive observational study, a total of 42 study subjects. The study subjects were non-small cell lung cancer patients undergoing first-line chemotherapy. Sociodemographic, clinical, and laboratory data analysis was carried out with the help of SPSS software in a univariate manner. Results: The study subjects were mostly male (85.36%), the age range of 40-60 years (66.67%), at risk of exposure from work (45.23%), smokers (59.52%), had a history of pulmonary TB (11.9%), history of COPD (2.38%), history of malignancy of other organs (2.38%) with the most cell type being adenocarcinoma (54.76%). The most common hematological side effects were first-degree anemia (21.43%) and first-degree leukopenia (21.43%). The most non-hematological side effects were first-degree alopecia (90.48%), followed by first-degree nausea and vomiting (78.57%). Conclusion: Chemotherapy side effects were found in all regimens given with mild degrees. The side effects obtained were in the form of hematological and non-hematological side effects.